Q5. From the sum of 2st+ s²+t² and 5st+3s²+3t²
Answers
Answered by
297
To calculate the sum :
- First step to write both the expressions together separated by an operational sign '+'
- Now,Arrange like terms together ( means term of Variable of same type should be together).
- At last add them which is our required answer.
Remember=>The and used between the given two expression signifies the 'sum'.
Now ,we will write the given two expression :
=>2st+s²+t² and 5st+3s²+3t²
=>2st+s²+t²+5st+3s²+3t²
Now ,write like terms together :
=>2st+5st+s²+3s²+t²+3t²
=>7st+4s²+4t²
=>7st+4s²+4t² is your answer.
Similar questions